APPLICATION DESIGN DETERMINING STUDENT ACHIEVEMENT SUPPORT FACTORS WITH THE TAU KENDALL METHOD BASED ON QUADRANT INSTITUTE LITERATURE - Hijrah Hijrah; Rahmat Musfikar (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2021)
There are many factors that can affect student achievement, both internal and external factors. To find out what factors can affect student achievement, each data factor that can affect student achievement is tested for correlation with the Kendall Tau method so that the strength and relationship between student achievement and the supporting factors can be measured the relationship between the two variables. In this study, the correlation test of student supporting factors was carried out based on data obtained from the Quadrant Institute for further implementation into software or applications that can be used by students, parents and also the qudrant institute in improving student achievement and by developing these applications. then all information needs related to improving student learning can be done by simply accessing the application that has been designed.Keywords : Student Achievement Factors, Correlation, Kendal tau, Applications Supporting Student Achievement